2009
DOI: 10.1080/10255840902718626
|View full text |Cite
|
Sign up to set email alerts
|

Stresses in cement mantles of hip replacements: effect of femoral implant sizes, body mass index and bone quality

Abstract: The effects of femoral prosthetic heads of diameters 22 and 28mm were investigated on the stability of reconstructed hemi-pelves with cement mantles of thicknesses 1-4mm and different bone qualities. Materialise medical imaging package and I-Deas finite element (FE) software were used to create accurate geometry of a hemi-pelvis from CT-scan images. Our FE results show an increase in cement mantle stresses associated with the larger femoral head. When a 22mm femoral head is used on acetabulae of diameters 56mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…We found that the highest average von Mises stresses occurred in the cortical bone of the superior and anterior periacetabular area of the pelvis. In addition, predictions from our model indicated that pelvic bone stresses are not significantly affected by femoral head implant size, a similar finding to that of Lamvohee et al…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the highest average von Mises stresses occurred in the cortical bone of the superior and anterior periacetabular area of the pelvis. In addition, predictions from our model indicated that pelvic bone stresses are not significantly affected by femoral head implant size, a similar finding to that of Lamvohee et al…”
Section: Discussionsupporting
confidence: 90%
“…The mechanical behavior within the cement mantle and at the bone‐cement interface, where debonding usually initiates, is affected by multiple factors including cement thickness, acetabular cup outer diameter, cup penetration, and inclination angle, bone quality, body mass index and femoral head size …”
mentioning
confidence: 99%
“…To date, only limited research has been undertaken into determining the effect of femoral head size on the cement mantle stresses. Lamvohee et al, using finite element (FE) modeling, investigated the stresses in the acetabular cement mantle resulting from the use of two femoral head sizes (22 and 28 mm). They found that under the loading condition of normal walking, the tensile stresses in the cement mantle increased by up 27% when femoral head size increased from 22 to 28 mm.…”
mentioning
confidence: 99%
“…A wide range of stiffnesses of the equivalent bone was covered by increasing and reducing the elastic modulus of the equivalent bone by 50 per cent, respectively. Although bone quality influences stress distribution in the cement mantle of hip replacement [29], no large differences in the lubrication performance were found in this study for equivalent bones with different elastic moduli, as shown in Fig. 10.…”
Section: Resultsmentioning
confidence: 55%